(untitled) (Research, Society and Development, 2022)
Introduction: Eating behavior is the conceptualization of the actions that the individual has before and during the meal, as well as where, what, with whom and when he eats and relates. It is known that stressors tend to influence diet, especially in students during the first years of study in higher education institutions. Objective: To evaluate the behavior and food consumption of students entering the Nutrition course. Method: This was a quantitative, analytical and cross-sectional study carried out at Centro Universitário Estácio do Ceará, with 65 students who were enrolled in the first semester of the Nutrition Course in 2019. Results: Most 69.2% (n=45) of the participants were female, 72.3% (n=47) did not frequently consume raw and/or cooked vegetables. Regarding restrictive eating behavior, there was a significant association (p=0.03) with the consumption of sausages, since students who had adequate consumption had a greater restriction behavior (27.62±9.9) in relation to those who consumed inappropriately (20.59±7.9). Conclusion: There is a need to carry out nutrition education with nutrition students regarding food intake and behavior.